Distributed Learning : Pedagogy and Technology in Online Information Literacy Instruction. - Maddison, Tasha (Chandos information professional series., 2016)
The field of distributed learning is constantly evolving. Online technology provides instructors with the flexibility to offer meaningful instruction to students who are at a distance or in some cases right on campus, but still unable to be physically present in the classroom. This dynamic environment challenges librarians to monitor, learn, adapt, collaborate, and use new technological advances in order to make the best use of techniques to engage students and improve learning outcomes and success rates. Distributed Learning provides evidence based information on a variety of issues, surrounding online teaching and learning from the perspective of librarians.